Canadians' access to cash before and during the COVID-19 pandemic - Heng Chen; Marie-Hélène Felt (Bank of Canada, 2022)
This paper studies Canadians' access to cash using the geographical distribution of automated banking machines (ABMs). We find that over 97% of urban Canadians have access to ABMs in their communities, while 92% of rural people have access to at least one ABM. During the pandemic, there have been no sustained adverse effects on cash accessibility through ABMs.
Keywords: J15; O1; R51; 330; Financial Services; Regional economic developments